Legal Protection Of Notaries In Issuing Skmht (Charge Letter Of Power Of Attorney Monitoring Rights) On The Bank - Dina Andiza; Beby Sendy; Moehammad Erwin Radityo; Lubis, Syna Ardia Putri (International Forum of Researchers and Lecturers, 2024)
Land as the wealth of the Indonesian nation must be utilized for the greatest prosperity of the people. To achieve this utilization, land consolidation needs to be carried out as an effort to increase the utility and results of land use and to align individual interests with the social function of land in the context of implementing development. Land is the basic capital for development and supports the running of the economy, there is almost no development activity that does not require land. Land plays a very important role, even determining the success or failure of a development. The nature of this research is descriptive, the results of this research are expected to obtain a factual picture or description of the land consolidation policy towards the re-arrangement of land ownership and use in Tanjung Sena Village, Sibiru-Biru District, Deli Serdang Regency, where the objects of land consolidation are land, residential buildings, dry land such as oil palms and fields, and village roads. Land consolidation as one of the efforts to increase the utility and results of land use. Land utilization needs to be implemented in the form of land regulation, control, and management. The use and utilization of land is carried out by re-arranging, partnership efforts, transfer and release of land rights in accordance with applicable laws and regulations. In the framework of land use management, guidance and control are carried out. Guidance is carried out through the provision of guidelines, guidance, training, and direction, while control is carried out through supervision such as supervision, reporting and regulation. The implementation of the regional spatial planning design is not always effective in the field, some people still assume that land rights are absolute rights, meaning rights that cannot be violated against land even though land rights contain social functions, land can be used by anyone as long as legal procedures have been taken, especially if the prospective land user is the state and is used for public interest.are fun for children such as singing, storytelling, role playing and involving parents in learning at home.